A utilização do plano de gestão de logística sustentável como ferramenta de gestão: um olhar dos servidores da Universidade Federal de Santa Maria - Gazzoni, Fernando (2014)
The sustainable logistics management plan was established by Decree 7746 of June 5, 2012, and with it all federal institutions were required to prepare logistic plans having sustainable development as the main point. For the success of this plan it is necessary to be incorporated into the organizational practices of each public administration servant. In the face of this situation and aiming to insert the plan and sustainable variable in UFSM organizational environment, the creation of action plans as main objective was defined. So we used a questionnaire to diagnose the profile of UFSM servants, assess the level of knowledge regarding sustainable issues and identify aspects considered the most important ones for the development of action plans. Besides, interviews were conducted with the setting-up committee of the PLS in UFSM in order to obtain a deepening of the process of design and its implementation. The results showed that the servants, regardless of individual factors, generally have a low level of knowledge on topics related to sustainability in public administration. Issues related to the development of sustainable construction projects, the realization of rational consumption campaigns and the re-use of materials were the main points raised by respondents as suggestions for preparing action plans. Later, the strengths and weaknesses in the organizational environment were identified in order to explore these aspects in planning actions. In the preparation of plans the aspects of the inclusion of them in the work routine had priority and enabled an initial discussion on the subject, as the level of knowledge is not satisfactory and it is essential to move forward on this discussion.